Математичні аспекти моделювання та планування діяльності агропромислових підприємств в умовах невизначеності - Нужна, Світлана Анатоліївна; Nuzhna, Svetlana (Дніпровський державний аграрно-економічний університет, 2016)
Запропоновано стохастичну економіко-математичну модель аграрного підприємства, а також концепцію оптимізації процесів агровиробництва в умовах невизначеності. Отримані результати можуть бути використані для розробки планів діяльності підприємств для будь-якої природно-економічної зони. Реальні розрахунки підтверджують економічну ефективність розробленої концепції планування. Stochastic economic-mathematic model of agricultural enterprise, the optimization concept of agricultural production processes under uncertainty are suggested in this article. The obtained results of research can be used for development plans of agricultural enterprises under uncertainty for any natural and economic zone. Real calculations prove economic efficiency of developed planning concept. It is proved that technical and economic indexes of agricultural enterprisemanufacture are largely dependent on the variability of weather and also on optimization criterion. Moreover the received technical and economic indexes of optimal plans make it possible to assess the economic risk of any index.Analysis of options designed on the model confirms that the application of mathematical methods gives economic strictly substantiated information to plan agricultural production and is very efficient. As a result of this approach, modeling reduced economic risk and mitigated the negative impact of weather conditions, created the structure of production, which in the face of uncertainty would be best adapted to possible changes.Collection and preparation of information required to build economic and mathematical model of production planning is a complicated and time-consuming process. The inability to obtain the necessary information regarding the research object or environment, unreliable information, and imperfect methods for calculation of technical and economic performance leading to lower quality plans. With the development of information technology there are new possibilities of obtaining, maintaining, using and analyzing information. The possibilities of modern information systems and technologies allow to generate significant amounts of specially organized collections of data complement and work with them.
Mathematical aspects of agricultural enterprises design and planning under uncertainty
Keywords: економічний ризик; economic risk; стохастична економіко-математична модель; stochastic economic-mathematical model; аграрні підприємства; agro-industrial enterprises; стратегічне планування; strategic planning; тактичне планування; tactical planning; критерій оптимальності; optimality criterion; техніко-економічні показники; technical and economic indexes; товарна продукція; commodity products; прибуток; profit; рентабельність; profitability